Distribution Patterns of Microplastics in Seawater Surface at a Portuguese Estuary and Marine Park - Rodrigues, Diana; Antunes, Joana; Otero, Vanessa; Sobral, Paula; Costa, Maria Helena (Frontiers in Environmental Science, 2020)
Measuring local levels of marine pollution by microplastics (MP) and identifying potential sources in coastal areas is essential to evaluate the associated impacts to environment and biota. The accumulation of floating MP at the sea surface is of great concern as the neustonic habitat consists of a feeding ground for primary consumers (including filter-feeders) and active predators, which makes these organisms a relevant via of MP input into the marine trophic chain. Here, a baseline evaluation of MP accumulation at the sea surface was conducted with a neuston net (335 µm mesh) at the Arrábida coastal area, in Portugal. The study site encompasses a marine protected area and an estuary, both under strong anthropogenic pressures due to multiple activities taking place. A short-term investigation on local spatiotemporal distribution, concentration and composition of MP was performed for the first time, through the monthly collection (summer 2018 to winter 2019) of samples at 6 stations. All the neuston samples contained MP and their mean concentration was 0.45 ± 0.52 items m-3 (mean ± SD). Both the averaged MP:neuston and MP:ichthyoplankton ratios were higher in December, when concentrations of organisms decreased. Temporal distribution patterns followed expected trends, as MP concentration was clearly higher in winter months due to precipitation and runoff. Although mean MP concentrations did not vary significantly between sampling stations, there was a spatial distribution of MP in relation to particle shape and size. Fragments were the most abundant shape and MP belonging to 1-2 mm size class were dominant. Amongst a diversity of 10 polymers identified by FTIR analysis, polyethylene (PE), polypropylene (PP) and copolymer PP/PE were the most abundant. Potential links between local sources/activities and the different polymers were suggested. Altogether, the information provided in this study aims to raise awareness among the identified sectors and consequently to act towards the prevention of MP inputs in the region.